Rationale for the evaluation of nintedanib as a treatment for systemic sclerosis–associated interstitial lung disease. Issue 3 (October 2019) - Wollin, Lutz; Distler, Jörg HW; Denton, Christopher P; Gahlemann, Martina
Interstitial lung disease is a common manifestation of systemic sclerosis. Systemic sclerosis–associated interstitial lung disease is characterized by progressive pulmonary fibrosis and a reduction in pulmonary function. Effective treatments for systemic sclerosis–associated interstitial lung disease are lacking. In addition to clinical similarities, systemic sclerosis–associated interstitial lung disease shows similarities to idiopathic pulmonary fibrosis in the pathophysiology of the underlying fibrotic processes. Idiopathic pulmonary fibrosis and systemic sclerosis–associated interstitial lung disease culminate in a self-sustaining pathway of pulmonary fibrosis in which fibroblasts are activated, myofibroblasts accumulate, and the excessive extracellular matrix is deposited. Nintedanib is a tyrosine kinase inhibitor that has been approved for the treatment of idiopathic pulmonary fibrosis. In patients with idiopathic pulmonary fibrosis, nintedanib slows disease progression by decreasing the rate of lung function decline. In this review, we summarize the antifibrotic, anti-inflammatory, and attenuated vascular remodeling effects of nintedanib demonstrated in in vitro studies and in animal models of aspects of systemic sclerosis. Nintedanib interferes at multiple critical steps in the pathobiology of systemic sclerosis–associated interstitial lung disease, providing a convincing rationale for its investigation as a potential therapy. Finally, we summarize the design of the randomized placebo-controlled SENSCIS ® trial that is evaluating the efficacy and safety of nintedanib in patients with systemic sclerosis–associated interstitial lung disease.